Jonathan Edwards on Justification : Reform Development of the Doctrine in Eighteenth-Century New England. - Cho, Hyun-Jin (University Press of America, 2012)
Jonathan Edwards (1703-1758) was a preacher, theologian, and missionary to the Native Americans. This book asserts that Jonathan Edwards stood firmly on the Reformed tradition in the doctrine of justification.